2015
DOI: 10.1159/000441579
|View full text |Cite
|
Sign up to set email alerts
|

Application of Continuous Renal Replacement Therapy: What Should We Consider Based on Existing Evidence?

Abstract: Background: Continuous renal replacement therapy (CRRT) is performed mainly in patients with acute kidney injury, severe sepsis, or septic shock. Evidence has emerged about the indications for and therapeutic conditions of CRRT. In this review, we focus on the evidence for CRRT to date. Summary: CRRT employs diffusion, convection and adsorption to remove solutes from plasma. Indications can be divided into renal and non-renal indications. Concrete renal indications have not yet been determined, except for life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The constant removal of solutes thus avoids sudden changes in plasma osmolality, especially in individuals with intracranial hypertension. Continuous modalities provide better adjustment of metabolic acidosis and metabolic control for hypercatabolic individuals, and induce possible immunomodulatory effects [2729]. …”
Section: Discussionmentioning
confidence: 99%
“…The constant removal of solutes thus avoids sudden changes in plasma osmolality, especially in individuals with intracranial hypertension. Continuous modalities provide better adjustment of metabolic acidosis and metabolic control for hypercatabolic individuals, and induce possible immunomodulatory effects [2729]. …”
Section: Discussionmentioning
confidence: 99%
“…Adsorption by the CRRT membrane represents a third mechanism of clearance. 23 The Prospective Pediatric CRRT (ppCRRT) Registry, a multicenter observational study of 370 children on CRRT, evaluated current practices in pediatric CRRT modality choice across centers and showed that all modalities are commonly utilized: 48% CVVHDF, 21% CVVH, and 30% CVVHD. 24 The role of CRRT in sepsis serves can be evaluated from two major aspects: renal replacement therapy for AKI and immunomodulation.…”
Section: Continuous Renal Replacement Therapymentioning
confidence: 99%
“…In Australia and New Zealand, the following specifications were reported: blood flow, 200 mL.min −1 and the amount of blood purification, 24.3 mL·kg −1 ·h −1 10. In Japan, the following procedure was reported: blood flow, 80 mL.min −1 and the median amount of blood purification, 16 mL·kg −1 ·h −1 11. These reports indicate that the values vary depending on the country, region, and institution.…”
Section: Introductionmentioning
confidence: 99%